RESEARCH BOOTCAMP TRAINING TO IMPROVE RESEARCH COMPETENCE AT THE MUHAMMADIYAH UNIVERSITY OF PALOPO, NAHDLATUL ULAMA UNIVERSITY OF INDONESIA, AND AL-AZHAR ISLAMIC UNIVERSITY OF MATARAM - Ati Sumiati; Tuty Sariwulan; I Gusti Ketut Agung Ulupui; Ika Febrilia; Rida Prihatni; Chusnanik Mufidah (International Journal of Engagement and Empowerment, 2023)
University is one of the centers of intellectual development in order to improve competitiveness, performance, and quality. However, universities need to make improvements, especially in research, because it is often found that lecturers and students have difficulties in writing articles and publications, especially those experienced by students on private campuses such as Muhammadiyah University of Palopo, Nahdlatul Ulama University of Indonesia, and Al-Azhar Islamic University Mataram. This activity is one of the efforts to overcome these problems. With this activity, it is hoped that participants can be helped in making articles by learning about accessing indexed national and international journals and using Quillbot software for paraphrasing